1999
DOI: 10.2486/indhealth.37.28
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Human Body Vibration Induced by Low Frequency Noise.

Abstract: To understand the basic characteristics of the human body vibration induced by low frequency noise and to use it to evaluate the effects on health, we designed a measuring method with a miniature accelerometer and carried out preliminary measurements. Vibration was measured on the chest and abdomen of 6 male subjects who were exposed to pure tones in the frequency range of 20 to 50 Hz, where the method we designed was proved to be sensitive enough to detect vibration on the body surface. The level and rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…The methods for measuring noise-induced vibration, which are briefly described in the following paragraphs, were almost the same as the methods used in our previous study [2]. The measurements were carried out in a test chamber with a capacity of about 25 m 3 [9] in winter (a dry season in Japan).…”
Section: Measurement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods for measuring noise-induced vibration, which are briefly described in the following paragraphs, were almost the same as the methods used in our previous study [2]. The measurements were carried out in a test chamber with a capacity of about 25 m 3 [9] in winter (a dry season in Japan).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…In our previous study we measured noise-induced vibration at the chest and abdomen of sitting subjects [2]. We found that the vibration acceleration levels of the noise-induced vibration measured at the chest were higher than those measured at the abdomen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The humidity in the test chamber was maintained at about 40% with a humidifier. To prevent changing the local vibrating system at the measuring position, we used a small (3.56 mm × 6.86 mm × 3.56 mm) and lightweight (0.5 g) accelerometer (EGA-125-10D, Entran, USA), with which we detected the vibration perpendicular to the body surface 11) . After being low-pass filtered and amplified with a strain amplifier (6M92, NEC San-ei Instruments, Japan), the output signal of the accelerometer was recorded on DAT by a multi-channel data recorder (PC216Ax, Sony Precision Technology, Japan).…”
mentioning
confidence: 99%
“…No noise stimulus in the frequency range higher than 50 Hz was used because the spatial uniformity of the sound pressure levels in the test chamber would deteriorate 10) . Noise stimuli lower than 20 Hz were not used because the noise-induced vibration was not distinguishable from the vibration inherent in the body surface 11) . The subject wore no clothes on the upper half of the body in order to allow the accelerometers to be attached.…”
mentioning
confidence: 99%